Balancing the load: A narrative review with methodological implications of compensatory training strategies for non-starting soccer players - Clemente, Filipe; Pillitteri, Guglielmo; Palucci Vieira, Luiz H.; Rabbani, Alireza; Zmijewski, Piotr; Beato, Marco (Biology of Sport, 2024)
New training approaches have emerged advocating for the implementation of compensatory physical training. This approach aims to provide additional training that balances the load typically experienced by non-starters during a match. This may help maintain their readiness and ensures that their physical fitness is not compromised by the reduced exposure to match loads. Thus, this narrative review aims to describe the differences in external loads between starting and non-starting players and describe the studies conducted in compensatory training. Studies examining external load metrics such as total distances covered, high-speed running, and sprinting suggest that, adjusted for playing time, values are often higher in non starting players. Although not standardized, there is an obvious decrease in exposure for these critical variables in non-starters. Additionally, internal load parameters such as perceived exertion and heart rate tend to be higher in starting players. Regarding the physical fitness impacts, evidence suggests differences observed between starters and non-starters in some aspects of physical performance, although the extent and significance of these differences can vary. The studies on compensatory training are limited, and the typical approach usually centres on running-based exercises and small-sided games, offering differing approaches to address the physical needs. The gap in research underscores the necessity for improved study designs that can shed light on the real impact of compensatory training. Presently, the practice of compensatory training has been adopted, yet a definitive understanding of its genuine influence, particularly in terms of enhancing physical fitness and mitigating injury risks, remains elusive.